Allogenic Fecal Microbiota Transplantation in Patients With Nonalcoholic Fatty Liver Disease Improves Abnormal Small Intestinal Permeability: A Randomized Control Trial - Craven, Laura; Rahman, Adam; Nair Parvathy, Seema; Beaton, Melanie; Silverman, Justin; Qumosani, Karim; Hramiak, Irene; Hegele, Rob; Joy, Tisha; Meddings, Jon; Urquhart, Brad; Harvie, Ruth; et al. (The American journal of gastroenterology, 2020)
Nonalcoholic fatty liver disease (NAFLD) is an obesity-related disorder that is rapidly increasing in incidence and is considered the hepatic manifestation of the metabolic syndrome. The gut microbiome plays a role in metabolism and maintaining gut barrier integrity. Studies have found differences in the microbiota between NAFLD and healthy patients and increased intestinal permeability in patients with NAFLD. Fecal microbiota transplantation (FMT) can be used to alter the gut microbiome. It was hypothesized that an FMT from a thin and healthy donor given to patients with NAFLD would improve insulin resistance (IR), hepatic proton density fat fraction (PDFF), and intestinal permeability. Twenty-one patients with NAFLD were recruited and randomized in a ratio of 3:1 to either an allogenic (n = 15) or an autologous (n = 6) FMT delivered by using an endoscope to the distal duodenum. IR was calculated by HOMA-IR, hepatic PDFF was measured by MRI, and intestinal permeability was tested using the lactulose:mannitol urine test. Additional markers of metabolic syndrome and the gut microbiota were examined. Patient visits occurred at baseline, 2, 6 weeks, and 6 months post-FMT. There were no significant changes in HOMA-IR or hepatic PDFF in patients who received the allogenic or autologous FMT. Allogenic FMT patients with elevated small intestinal permeability (>0.025 lactulose:mannitol, n = 7) at baseline had a significant reduction 6 weeks after allogenic FMT. FMT did not improve IR as measured by HOMA-IR or hepatic PDFF but did have the potential to reduce small intestinal permeability in patients with NAFLD.